2021
DOI: 10.1029/2021gl093796
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Loading and Radiation Budget Perturbations in Densely Populated and Highly Polluted Indo‐Gangetic Plain by COVID‐19: Influences on Cloud Properties and Air Temperature

Abstract: In the past, short-term/city-scale pollution reduction campaigns, such as "Olympic Blue" for 2008 Beijing Summer Olympic Games (Wang et al., 2010) and "APEC Blue" for 2014 Asia-Pacific Economic Cooperation (APEC) Economic Leaders' meeting (Huang et al., 2015), showed improvements in air quality after

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
(77 reference statements)
2
3
0
Order By: Relevance
“…Further, the decrease of CTH causes cloud top temperature to increase, enhancing cloud top radiative cooling to further facilitate CTH decrement. On the other hand, CF increases with the increase of AOT in all atmospheric regimes similar to a large volume of past studies performed at different regions of the earth (Khatri et al., 2021; Menon et al., 2008; Quaas et al., 2010; Sekiguchi et al., 2003). A broad range of mechanisms, including ACI process, meteorological factors, cloud droplet evaporation, and so on, can facilitate the increase of CF with the increase of AOT (Quaas et al., 2010; Su et al., 2008).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Further, the decrease of CTH causes cloud top temperature to increase, enhancing cloud top radiative cooling to further facilitate CTH decrement. On the other hand, CF increases with the increase of AOT in all atmospheric regimes similar to a large volume of past studies performed at different regions of the earth (Khatri et al., 2021; Menon et al., 2008; Quaas et al., 2010; Sekiguchi et al., 2003). A broad range of mechanisms, including ACI process, meteorological factors, cloud droplet evaporation, and so on, can facilitate the increase of CF with the increase of AOT (Quaas et al., 2010; Su et al., 2008).…”
Section: Resultssupporting
confidence: 85%
“…
Aerosols, tiny suspended particles in the atmosphere, are known to have profound impacts on climate system and hydrological cycle (Ramanathan et al, 2005;Rosenfeld et al, 2008) via two broad pathways: aerosol-radiation interaction (ARI) and aerosol-cloud interaction (ACI). In the former, aerosols scatter and absorb solar and terrestrial radiation (Khatri et al, 2009(Khatri et al, , 2021Wang et al, 2014); and in the latter, these aerosols form cloud condensation nuclei (CCN) and ice nuclei (IN) to modify cloud properties (Khatri et al, 2022;Sekiguchi et al, 2003;Twomey, 1974Twomey, , 1977. Overall, these processes have net cooling effect to offset global warming effect of greenhouse gases (Ramanathan et al, 2005), although the net cooling effects of these processes are still subject of large uncertainties.
…”
mentioning
confidence: 99%
“…Although such manifold factors can be responsible for differences in CER values between the SGLI and sky radiometer, most of the data samples show higher CER values from SGLI than from the sky radiometer, resulting in negative values of MBE for both water and ice clouds. This result is in line with previous studies that showed higher values from satellite observations compared with values obtained from surface and/or aircraft observations (e.g., Painemal and Zuidema, 2011;Chiu et al, 2012;King et al, 2013).…”
Section: Overall Comparisonsupporting
confidence: 93%
“…Anthropogenic aerosols can act as cloud condensation nuclei (CCN), increase the cloud droplet number concentration (Andreae, 2008; Haywood & Boucher, 2000; Ramanathan et al., 2002), modify the cloud liquid water path (Hill et al., 2009), limit the cloud droplet size under a certain liquid water path, and affect the albedo (Twomey, 1977), life, and area (Albrecht, 1989) of clouds. Therefore, the increase of aerosol loading has great impacts on the radiation budget (Haywood & Shine, 1995; Kim & Ramanathan, 2008), cloud properties (Khatri et al., 2021; Stevens & Feingold, 2009; Yang et al., 2019) and types, intensities, and distributions of precipitation (Cao et al., 2021; Jiang et al., 2016).…”
Section: Introductionmentioning
confidence: 99%